Hydraulics in Civil Engineering A Course with Experiments and Open-Source-Codes - Rapp, Christoph; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
The book serves a dual purpose. Firstly, it bridges the divide between applied civil engineering hydraulics and conventional fluid mechanics literature. Secondly, it is structured as a modular course, allowing for flexible application. The goal is to present information in a clear and illustrative manner, utilizing readily available materials, experiments, and open-source code examples. This is an open access book. The content is accompanied by code examples for open-source software includes descriptive explanations, illustrative experiments and easy-to-understand examples combines Sustainable Development Goals SDG4 and SDG 6: access to water and sanitation, respectively The author Dr. Christoph Rapp was a research assistant at the Chair of Hydraulics and Hydrology and later the Department of Hydromechanics at the Technical University of Munich. After earning his doctorate, he served as the head of the laboratory. In addition to experimental research into complex flows, he devoted himself to illustrative teaching. He received several prizes for this, including the Ernst Otto Fischer Teaching Prize for an innovative teaching concept. In the context of his collaboration with Markus Heinsdorff, he inspires with installation art about water. Christoph is head of the hydropower department of an energy supplier and lectures at Bauhaus University, Weimar . He also teaches at universities in developing countries through the International Knowledge Exchange Association, which he founded (Verein zur Förderung des internationalen Wissensaustauschs e.V. ).
About water -- Part I: Fundamentals and derivations -- Essential mathematics -- Essential physics -- Introduction to potential theory -- Basic equations -- Turbulence and its modelling -- Part II: Applied hydraulics -- Hydrostatics -- Bernoulli equation and energy diagrams -- Outflow from openings -- Momentum equation -- Steady pipe flow -- Unsteady pipe flow -- Steady free surface flow -- Unsteady free surface flow -- Introduction to groundwater flow -- Excercises -- Practical Examples.
Keywords: Environmental engineering; Civil engineering; Hydraulic engineering; Water; Hydrology; Environmental Civil Engineering; Hydraulic Engineering; Water